Multisociety consensus quality improvement guidelines for intraarterial catheter‐directed treatment of acute ischemic stroke, from the American Society of Neuroradiology, Canadian Interventional Radiology Association, Cardiovascular and Interventional Radiological Society of Europe, Society for Cardiovascular Angiography and Interventions, Society of Interventional Radiology, Society of NeuroInterventional Surgery, European Society of Minimally Invasive Neurological Therapy, and Society of Vascular and Interventional Neurology. Issue 2 (3rd May 2013) - Sacks, David; Black, Carl M.; Cognard, Christophe; Connors, John J.; Frei, Donald; Gupta, Rishi; Jovin, Tudor G.; Kluck, Bryan; Meyers, Philip M.; Murphy, Kieran J.; Ramee, Stephen; Rüfenacht, Daniel A.; et al.
<x xml:space="preserve">Abstract</x> Purpose In this international multispecialty document, quality benchmarks for processes of care and clinical outcomes are defined. It is intended that these benchmarks be used in a quality assurance program to assess and improve processes and outcomes in acute stroke revascularization. Materials and Methods Members of the writing group were appointed by the American Society of Neuroradiology, Canadian Interventional Radiology Association, Cardiovascular and Interventional Radiological Society of Europe, Society of Cardiac Angiography and Interventions, Society of Interventional Radiology, Society of NeuroInterventional Surgery, European Society of Minimally Invasive Neurological Therapy, and Society of Vascular and Interventional Neurology. The writing group reviewed the relevant literature from 1986 through February 2012 to create an evidence table summarizing processes and outcomes of care. Performance metrics and thresholds were then created by consensus. The guideline was approved by the sponsoring societies. It is intended that this guideline be fully updated in 3 years. Results In this international multispecialty document, quality benchmarks for processes of care and clinical outcomes are defined. These include process measures of time to imaging, arterial puncture, and revascularization and measures of clinical outcome up to 90 days. Conclusions Quality improvement guidelines are provided for endovascular acute ischemic stroke revascularization procedures. © 2013 Wiley Periodicals, Inc.